Determinants of Utilization of Antenatal Care Services by Pregnant Women at the Berastagi Health Center in Karo District in 2019 - Sibagariang, Eva Ellya; Marlinang I. Silalahi (TOUR HEALTH JOURNAL, 2023)
Purpose: One of the risk factors for maternal mortality and morbidity is the undetected danger signs during pregnancy due to irregular ANC visits. The coverage of health services for visits by pregnant women K1 and K4 at the Berastagi Health Center has not reached the target set by the Karo District Health Office. Based on data for the last 3 months at the Berastagi Garden Health Center in 2019, the coverage of ANC services with the target number of pregnant women was 1158 (100%) (K1 and K4), namely in April K1 87 (7.5%) and K4 81 (7.0%), in in May KI 82 (7.1%), K4 80(6.9%), in June K1 80 (6.9%) K4 79 (6.8%). This coverage has not yet reached the minimum district/city health service standards. This study aims to determine whether "Determinants of Utilization of Antenatal Care Services by Pregnant Women at the Berastagi Health Center in Karo District in 2019". Method: This study used the Cross Sectional method with an analytical survey, with a total sample of 71 people. This study used the chi-square test data analysis method to determine a significant relationship between knowledge, husband/family support and health worker support. Results: The results of this study indicate that there is a relationship between knowledge, husband/family support (p=0.000), and health worker support (p=0.001) towards the utilization of antenatal care services where the p-value is below 0.05. Disscusion and Conclusion: In response to this, it is suggested to health workers, especially midwives, to remain active in providing support and motivation as well as counseling about the benefits of routine prenatal checks for pregnant women so that pregnant women have the willingness to have their pregnancies checked at the puskesmas.